Entre tempos e história da arte: por um processo de apropriação - Marilda Oliveira de Oliveira; Carin Cristina Dahmer (EccoS – Revista Científica)
In this article is searched to approach time, the history of art and the images of the past that compose it. The process of appropriation is presented as a conceptual alternative, which by the dissemblance provide means to problematize the images. Accordingly, it generates a dialogue with Deleuze and Guattari (2011; 2005), Cherem (2009 ) e Archer (2012), searching pathways or tracks for the dynamic between the debris of the readings and the teaching experiences. Approaching the history of art not by its chronology or linearity, some breaches are sought out between past and present, in between-times that cross themselves. To achieve that, a cartography is used as a methodological possibility to articulate the interposing times in trajectories and teaching experiences with the images of the past. Stands out, as a result of this research the images that surround us as debris orbiting the space-time, and that erupt in fractures and breaches potencializing other senses for the present time.